QueerZazouZine : fanzine homosexuel, bi et autres d'expression, d'information et d'opinion (Bruxelles: Libre Différent Autonme)
"Fonds Suzan Daniel (FSD)Périodicité :Rédaction : LDA, 47 rue d'Albanie, 1060 Bruxelles"